español - Andino, Lucas (Ánima, 2022)
This article is an effort to advance a philosophical concept of silence. Properly, this investigation does not present an object, it only delineates the field through which this object has the possibility of manifesting itself. Our "object" is silence. Through a discussion and revaluation of related concepts, silence is glimpsed here as that instance that allows an essential saying to occur, an expression that we could affirm is the closest to silence since it manages to amalgamate discourse and language, existentiality and intramundaneity. The reader will notice that the playing field outlined here is one that is based, mainly, on Heidegger and that takes examples from the poetic work of Hugo Mujica; It should be noted, however, that this is not a study on silence in the works of the German author and the Argentine author.